Kenya's and Zambia's Relations with China 1949-2019 - Sun, Jodie Yuzhou (Eastern African studies (London, England), 2023)
Examines the history of post-colonial Kenya's and Zambia's relations with the People's Republic of China from ideological, political, economic and social perspectives.